DAMPAK CITRA SELEBRITI TERHADAP CITRA PRODUK YANG DIIKLANKANNYA - ASEP HERMAWAN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 1999)
The aim of this paper is to show the relevance of using celebrities as products endoser. It examines the theory and empirical papers underlying the hiring and firing of celebrity endosers. It also explores the implication for managers and future research.